The Equity Premium Puzzle in China - Ni, Zhiqi (2006)
The dissertation concentrates on one of the most famous puzzles in asset pricing, the equity premium puzzle, which is first identified by Mehra and Prescott (1985). It studies the existence and extent of the equity premium puzzle in China, which is still under controversy according to the existing literature. The abundant theories and explanations put forward in the western markets about the puzzle are introduced and Chinese empirical data are used for testing the puzzle in the study.